P68-F Abnormalities of cortical neural synchronization mechanisms in patients with Alzheimer's diseases dementia: An EEG study. Issue 7 (July 2019) - Karami, Vania; Amenta, Francesco; Noce, Giuseppe; Percio, Claudio Del; Lizio, Roberta; Pascarelli, Maria Teresa; Blūma, Marina; Babiloni, Claudio
Abstract : Background: This retrospective study aimed to check whether the resting state eyes-closed electroencephalographic (rsEEG) rhythms might reflect brain arousal in patients with Alzheimer's disease dementia (ADD) at the group and the individual level. Methods: Our dataset was an international archive of Clinical and rsEEG data of 42 ADD and 40 healthy elderly (Nold) subjects. The delta, theta, alpha 1, alpha 2, and alpha 3 frequency bands were determined by Individual alpha frequency peak (IAF). Fixed beta 1, beta 2, and gamma bands were also considered. rsEEG cortical sources were estimated by means of the exact low-resolution brain electromagnetic source tomography and were then classified across individuals, on the basis of the receiver operating characteristic (ROC) curves. Results: Compared to the Nold group, IAF showed slowing in the ADD group. Furthermore, The ADD group showed lower posterior alpha 2 source activities and higher occipital delta source activities. The ratio of occipital delta to alpha 2 allowed good classification accuracy (sensitivity: 88.1%, specificity: 85%, and accuracy: 86.6%) between the Nold and ADD individuals. Conclusion: In quiet wakefulness, delta and alpha sources unveiled different spatial and frequency features of the cortical neural synchronization underpinning brain arousal in ADD patients compared with Nold subjects. An ongoing study is testing the enrichment of markers derived from structural magnetic resonance imaging (MRI) in the classification accuracy between Nold and ADD patients for potential clinical applications.